A corpus-based study of the AAAL conference handbook. Issue 23 (September 2016) - Simon-Maeda, Andrea
Abstract: This corpus-based study examines the use of interpersonal metadiscourse devices in eight American Association of Applied Linguistics (AAAL) conference handbooks spanning the years 2007–2014. A concordance program (CasualConc) was used to search for recurring patterns in the AAAL corpus and to compare the results with a corpus compiled from conference handbooks of four different hard disciplines. Of particular interest was whether or not the pattern it + passive reporting verb + that -clause; for example, it is argued that rather than I argue that figured significantly in the corpora. Previous research has suggested that impersonal it and the passivization of the reporting verb function to depersonalize propositions put forth in academic writing and that this language choice is one feature of an objective, as opposed to a subjective, academic writing style. The frequency findings for the AAAL corpus indicated an overwhelming usage of three interpersonal metadiscourse structures ( I argue that, we argue that, it was found that ), while the pattern we show that was most prevalent in the hard disciplines corpus. The study concludes with a discussion of how knowledge-making practices are crafted through particular discourse conventions in order to establish one's insider status within an academic community. Highlights: Corpus analysis identifies specific metadiscourse items in conference summaries. Agentless reporting verbs in summaries function to depersonalize knowledge claims. Successful AAAL conference program submissions employ discipline-approved language. Comparison of soft and hard disciplines highlights specific metadiscourse devices. Writing conventions are imbedded in epistemological stances concerning knowledge.